2016
DOI: 10.1128/aac.01922-15
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondrial RNA Polymerase in the Toxicity of Nucleotide Inhibitors of Hepatitis C Virus

Abstract: Toxicity has emerged during the clinical development of many but not all nucleotide inhibitors (NI) of hepatitis C virus (HCV). To better understand the mechanism for adverse events, clinically relevant HCV NI were characterized in biochemical and cellular assays, including assays of decreased viability in multiple cell lines and primary cells, interaction with human DNA and RNA polymerases, and inhibition of mitochondrial protein synthesis and respiration. NI that were incorporated by the mitochondrial RNA po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
103
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 41 publications
6
103
0
Order By: Relevance
“…In this study, we aimed to look more closely at correlates of cytotoxicity with BMS-986094 treatment in order to better understand the lack of cytotoxicity ob- served with DAPN phosphoramidate prodrugs. It was recently reported that human mitochondrial RNA polymerase (POLRMT) incorporates 2=-C-methyl-GTP as well as a number of other anti-HCV ribonucleoside analogs (32,33). Here, we show that 2=-Cmethyl-DAPN-TP is also a substrate for POLRMT (Fig.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…In this study, we aimed to look more closely at correlates of cytotoxicity with BMS-986094 treatment in order to better understand the lack of cytotoxicity ob- served with DAPN phosphoramidate prodrugs. It was recently reported that human mitochondrial RNA polymerase (POLRMT) incorporates 2=-C-methyl-GTP as well as a number of other anti-HCV ribonucleoside analogs (32,33). Here, we show that 2=-Cmethyl-DAPN-TP is also a substrate for POLRMT (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Primary human hepatocytes were estimated to contain amounts of natural NTPs comparable to those of Huh-7 cells. Nucleotide levels measured by LC-MS/MS were converted to micromolar concentrations, estimating a cell volume of 2 pl/cell (33). b Intracellular 2=-C-methyl-DAPN-TP and 2=-C-methyl-GTP levels measured in primary human hepatocytes after treatment with 50 M DAPN-PD1 for 24 h. c Rate constant for incorporation was determined with the equation…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations